Information Security Awareness Analysis on Digital Bank Customer Using Analytic Hierarchy Process: Case Study at XYZ Application from Bank ABC - Kemas Khaidar Ali Indrakusuma; Achmad Nizar Hidayanto (Universitas Islam Negeri Walisongo Semarang, 2023)
Digital banking is an innovation from banks to deal with the high demand of the retail customer. This study aims to analyse and measure the level of information security awareness of the customers of XYZ as one of the digital banks in Indonesia and provide recommendations for steps that need to be taken to reduce fraud cases caused by customer negligence. Focus areas that included in this research are the adaptation and extension of the HAIS-Q framework and becoming a new theoretical framework to measure information security awareness for end-user. The measurement is carried out by distributing questionnaires with five Likert scales to 385 respondents and then processed using the Analytic Hierarchy Process (AHP) method which involves eight experts measuring the weight of several identified focus areas and then classified using the Kruger scale. The information security awareness measurement has a result of 81,9770 which indicates that the information security awareness of XYZ users has a good level. The results of data processing show that there are two focus areas and ten focus sub-area that is still not in the good category. In addition, several recommendations are given to XYZ so that the focus areas and sub-areas that are not categorized as good can be improved to make sure the information security awareness of XYZ users becomes better.